The Association between Peripheral Th17, Th1, IL-17, and IFN-γ Levels and TACE Response in Patients with Unresectable Hepatocellular Carcinoma with or without Cirrhosis - Irsan Hasan; Rino A Gani; Laurentius A Lesmana; Siti B Kresno; Jacub Pandelaki; Suhendro Suwarto (Interna Publishing, 2020)
Background: Th17 cells, a subset of CD4+ T cells with the capacity to produce IL-17, were reported to have pro-tumor and anti-tumor effects. Th1 cells are known for their capacity to eliminate tumor cells by producing IFN-γ. Transarterial chemoembolization (TACE) is a treatment of choice for patients with unresectable hepatocellular carcinoma (HCC). Therefore, this study aimed to determine the association between peripheral Th17, Th1, IL-17, and IFN-γ levels and TACE response in patients with unresectable HCC with or without cirrhosis. Methods: a prospective cohort study was conducted in Cipto Mangunkusumo Hospital and several affiliated hospitals from June 2015 to January 2019. HCC patients with or without cirrhosis who met the inclusion criteria were included in this study. Blood samples were obtained immediately before TACE and 30 days after TACE. Th1 and Th17 cells were analyzed by flowcytometry, while IL-17 and IFN-γ were examined with ELISA method. TACE response was assessed with mRECIST. Results: forty-one HCC patients were enrolled in this study. According to mRECIST, 12 patients were assessed as response group (complete and partial response) and 29 patients were assessed as nonresponse group (stable and progressive disease). Levels of Th1 and Th17 increased significantly after TACE in the response group. On the other hand, IL-17 and IFN-γ decreased after TACE in both groups, although not statistically significant. Interestingly, in the response group, a significant increase was found in the number of T cells subset showing both IFN-γ and IL-17 markers on their surfaces, i.e. CD4+/IFN-γ+/IL-17+ T cells. Conclusion: increased circulating Th1, Th17, and CD4+/IFN-γ+/IL-17+ T cells were observed in HCC patients with complete or partial response to TACE.